Entrepreneurial orientation and business performance: A study on micro and small entrepreneurs of Assam - et. al., Hiranyamayi Majumder, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Entrepreneurship is a vital source of growth and development in an economy. The multifaceted phenomenon of the term entrepreneurship makes it a streaming subject to enquire about its inevitability and universal applicability. The present paper is a similar attempt to study the exponential term entrepreneurial orientation and its relationship with firm performance in selected SMEs of Assam. After reviewing the literature, we came up with a set of agreed dimensions of EO i.e. innovativeness, proactiveness, autonomy, competitive aggressiveness, and risk-taking propensity. We tested a sample of 100 micro and small firms that had been in business for more than five years with a schedule consisting set of statement questions. Regression analysis was used to test the relationship between entrepreneurial orientation and firm performance that found a significant positive effect among the two. It can be concluded that entrepreneurial orientation of Micro and Small owners/managers can influence the success and survival of the SMEs.